2021
DOI: 10.1002/adfm.202105544
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic 4D‐Printed Breathing Hydrogel Actuators by Nanothylakoid and Thermoresponsive Polymer Networks

Abstract: Shape-morphing actuators, which can breathe with the accompany of morphology changes to mimic botanical events, are challenging to fabricate with soft hydrogel materials. Herein, 4D printed-smart hydrogel actuators are reported that can not only dynamically deform but also generate oxygen (O 2 ) upon external stimulations. The printed breathing actuators featured with spinach leaf-derived thylakoid membrane (nanothylakoid) for photothermal conversion and catalytical O 2 evolution, a poly(N-isopropylacrylamide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 48 publications
(43 reference statements)
0
37
0
1
Order By: Relevance
“…The reversible swelling‐deswelling property of hydrogels by stimuli can be exploited to produce macroscopic actuation for soft robots. A large variety of stimuli, such as heat, [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ] light, [ 150 , 151 , 152 , 153 ] water, [ 154 , 155 ] pH, [ 156 , 157 , 158 ] biomolecules, [ 159 , 160 ] and electric field, [ 157 , 161 , 162 , 163 ] can change the osmotic pressure of solvents in hydrogels and/or environments, resulting in water diffusion in or out of the hydrogels, corresponding to their expansion or contraction, respectively. [ 164 ] Other than common physical stimuli, a recent study showed that a hydrogel robot could locomote on water surface for 3.5 h by the Marangoni effect (Figure 5e ).…”
Section: Biomimetic Functions and Potential Applicationsmentioning
confidence: 99%
“…The reversible swelling‐deswelling property of hydrogels by stimuli can be exploited to produce macroscopic actuation for soft robots. A large variety of stimuli, such as heat, [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ] light, [ 150 , 151 , 152 , 153 ] water, [ 154 , 155 ] pH, [ 156 , 157 , 158 ] biomolecules, [ 159 , 160 ] and electric field, [ 157 , 161 , 162 , 163 ] can change the osmotic pressure of solvents in hydrogels and/or environments, resulting in water diffusion in or out of the hydrogels, corresponding to their expansion or contraction, respectively. [ 164 ] Other than common physical stimuli, a recent study showed that a hydrogel robot could locomote on water surface for 3.5 h by the Marangoni effect (Figure 5e ).…”
Section: Biomimetic Functions and Potential Applicationsmentioning
confidence: 99%
“…Recently, Wang and co‐workers fabricated a photoactive actuator via 3D printing ( Figure ). [ 322 ] A thermoresponsive PNIPAM‐based layer loaded with spinach‐leaf‐derived nanothylakoid was combined with a PAA layer. The nanothylakoid was introduced to enable photothermal conversion and oxygen evolution.…”
Section: Applicationsmentioning
confidence: 99%
“…a) Formation via 3D printing, b) final flower-shaped two-layer hydrogel (crosslinked PNIPAM/PAA with 3:1-layer ratio),and c) movement of the flower-shaped actuator to grab a moving object. Reproduced with permission [322]. Copyright 2021, Wiley-VCH GmbH.…”
mentioning
confidence: 99%
“…Smart actuators that can transform other forms of energy into mechanical deformation from external stimuli such as heat, light, electricity, magnetism, solvent, pH, and humidity have been widely studied due to their potential applications in soft robotics, biomedical devices, haptic feedback systems, and so on. To date, substantial efforts have been devoted to developing flexible actuators based on various active materials such as electroactive polymers (EAPs), ,, shape memory polymers (SMPs), liquid crystal elastomers (LCEs), , hydrogels, , and bimorph nanocomposites. ,, Among these actuating materials, stimuli-responsive bimorph nanocomposite-based flexible actuators have recently come to the fore due to their simple structure, low production cost, high stability, and so on. , Unlike other previously mentioned flexible and soft actuators, the principal actuation mechanism for these bimorph actuators is attributed to asymmetric deformation at the interfaces due to their mismatched thermal, mechanical, and electrical properties . To date, many materials such as carbon nanotubes (CNTs), ,,, graphene, ,, graphene oxide, , and poly­(3,4-ethylene­dioxythiophene):polystyrene sulfonate (PEDOT:PSS) , have been utilized in bimorph flexible actuators.…”
Section: Introductionmentioning
confidence: 99%